1992
DOI: 10.1007/bf00713938
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to a revision of the genusTrichosporon

Abstract: The genus Trichosporon was revised using characters of morphology, ultrastructure, physiology, ubiquinone systems, mol% G + C of DNA, DNA/DNA reassociations and 26S ribosomal RNA partial sequences. A total of 101 strains was used, including all available type and authentic cultures of previously described taxa. Nineteen taxa could be distinguished, 15 of which having Q-9 coenzyme systems and 4 having Q-10. Sixteen previously described names were reduced to synonymy. One new species was described. The genus is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
1
19

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(174 citation statements)
references
References 51 publications
7
146
1
19
Order By: Relevance
“…As for trichosporonosis, Trichosporon cutaneum (or T beigelii) has long been believed to be the causative agent of this infection. A 28S rDNA sequence analysis by Gueho et al (4) clearly revealed the intraspecific heterogeneity of this species. On the basis of this result, some authors subsequently demonstrated that the major causative agent of trichosporonosis differs in each type of infection (3,5,19,20).…”
Section: Discussionmentioning
confidence: 87%
“…As for trichosporonosis, Trichosporon cutaneum (or T beigelii) has long been believed to be the causative agent of this infection. A 28S rDNA sequence analysis by Gueho et al (4) clearly revealed the intraspecific heterogeneity of this species. On the basis of this result, some authors subsequently demonstrated that the major causative agent of trichosporonosis differs in each type of infection (3,5,19,20).…”
Section: Discussionmentioning
confidence: 87%
“…beigelii (T. cutaneum) was initially reported as the causative agent of this disease. However, it was reclassified into 20 species by the molecular evolution classification system, based on DNA-DNA homology, introduced by Guého et al in 1992 [5]. According to the new classification, the species most often associated with deep-seated trichosporonosis are T. asahii and T. mucoides [6]; these are also the major causative agents of the summer-type of hypersensitivity pneumonitis.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcus (Table 5), the species with highly similar values of the sequences (3,8,9,15) had the same response to the mycocin. This congruence between data on rRNA sequences and mycocin sensitivity suggest that the latter character reflects the phylogenetic relation between yeasts.…”
Section: Discussionmentioning
confidence: 91%